Dampak Kegiatan Ekonomi terhadap Lingkungan : Sebuah Analisis Emisi Gas Rumah Kaea Indonesia - Hairin Fajeri; Maryunani Maryunani; Zainal Fanani; Luthfi Fatah (Universitas Lambung Mangkurat, 2015)
This paper is intended as part of efforts to mitigate climate change through the analysis of both the emission of GHG emissions in the past and future emissions. To detennine the sectors that have the potential to reduce emissions and make the emission reduction scenarios. The analysis was performed by the method of decomposition and emission projections. Emission intensity is a measure of the level of emissions per unit of economic activity (as measured by GDP). By comparing the change in the emission intensity of fossil fuels, and GOP. Indonesia's emissions from burning fossil fuels is growing faster than GDP during the decade 1970-2010, so that the emission intensity increases. But Indonesia's emissions intensity also increased sharply from 1970-2010-2 percent per year.Changes in average annual population, GDP per capita, energy intensity and carbon intensity, that in the long term for C02 emissions in Indonesia is increasing carbon intensity. The average annual growth of carbon intensity in Indonesia is relatively high, the annual energy intensity in Indonesia is in the right direction, albeit less progressive. Indonesia's carbon intensity (kg per kg of fuel use eq. Energy) 1.5 kg in 1990 to 2.1 kg in 2010.Looking at C02 emissions by sector, that industrial activity has become a major source of C02 emissions, one of the reasons is that the increasing number of companies in the industry. C02 emissions from the transportation sector grew steadily but lower than the industrial sector. It is interesting that the emissions from the electricity sector grew most rapidly since the mid-1990s. C02 emissions from the residential sector grew the slowest, perhaps reflecting the growing of household electrification. The share of emissions by sector shows the same thing: is the largest industry, electricity is the fastest growing. While total emissions have grown by about 7.5 percent per year, emissions from electricity grew approximately 11 percent I year in the last two decades.Emission reduction potential in the sector, there are 34 sectors of the economy that have the potential to reduce emissions such as electricity, mining, agriculture, forestry, industry, transport and others. Baseline, through decomposition analysis with known emission rate of change of 9. 5% per year and the amount of emissions by 2010, 410 million tC02e then emissions by 2020 if no intervention would be 799 million tons. Emission reduction scenarios by 2020, without intervention would be 799 million tons, with a reduction of 26% (208 million tC02e) then becomes 591 million tC02e emissions; and a reduction of 41% (328 million tC02e), the emissions would be 471 million tC02e.